Strategi Konten Reels Instagram @pemkotbogor dalam Meningkatkan Kualitas Informasi Publik Kota Bogor - Nurhaliza, Nazwa; Bachtiar, Willy (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This study aims to analyze the Instagram Reels content strategy implemented by the official account of the Bogor City Government (@pemkotbogor) in improving the quality of public information. Using a descriptive qualitative approach, data were collected through in-depth interviews, observations, and documentation with the public relations team of Bogor City and analysis of published Reels content. The findings indicate that the communication strategy follows the public relations model of Cutlip, Center, and Broom, which includes fact finding, planning, communication, and evaluation. This strategy is effective in engaging audiences through visually appealing content, light narratives, and the utilization of current social media trends. However, challenges such as limited human resources and the demand for real-time content publication were also identified. In conclusion, the use of Reels as a medium for public information dissemination represents a strategic approach that enhances engagement, strengthens institutional image, and improves the accessibility of information for the public.